A systematic evaluation of methods used and the effectiveness of health education interventions to improve knowledge, beliefs, and practices of cervical cancer screening - Al-Oseely, Sarah Ahmed; Abdul Manaf, Rosliza; Ismail, Suriani (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Screening of cervical cancer had decreased its morbidity and mortality in developed countries. Health education interventions are expected to enhance knowledge, attitude and practice of screening. Their success rely on designs and methods. Thus, this systematic review aims to identify the methods used and the effectiveness of health education interventions in improving knowledge, beliefs, and practices of cervical cancer screening among women of reproductive age. Methods: A systematic review of all published eligible studies in (PubMed, Science Direct and MEDLINE) databases from 1st of January 2016 to 31st of October 2020 was run using different keywords. A total of 14 research articles were included. The quality and risk of bias of studies was assessed by using EPHPP and the average score was given accordingly. This study was registered in PROSPERO (record #CRD42020188462). Results: The review combined 14 studies. Five studies were conducted in the USA, two in Hong Kong, one in Korea, one in England, one in Denmark, one in Norway, one in Turkey, one in Malaysia and one in Tanzania. Almost all interventions boosted the knowledge, attitude or screening uptake. Conclusion: This review showed that the most popular methods of delivering health intervention were health talk, Group discussion and pamphlet. Health education interventions was effective in improving the knowledge, attitude and screening uptake. Although, this effect differs according to methods of delivery, study background and populations. Therefore, it is better to understand the existing situation to develop the best intervention and more studies are needed to recognise barriers to screening.